Synthesis of Surfactant-Supported Algerian Clay for the Adsorption of Ni (II) in Water Media - Fedlaoui, Zahra; Mahmoud Charef; Abdelkader Ouakouak; Mohamed Benabdallah Taouti (International Journal of Integrated Engineering, 2025)
The purpose of this research is to prepare HDTMA-modified Algerian clay (HDTMA-Ac) and examine its ability to adsorb ions of nickel in water media. Characterization techniques such as X-ray diffraction, FTIR spectroscopy, thermogravimetric analysis (TGA), and the point of zero charges (pHpzc) were used to analyse the sample properties. The adsorption capacity of HDTMA-Ac towards Ni (II) ions was investigated under several operating conditions, such as pH and initial concentration of Ni (II). Results showed that the raw clay was successfully modified by intercalation of the surfactant ions in the interlayer space of clay. The maximum removal efficiency of Ni(II) on HDTMA-Ac was found to be 95.71, 84.47, 72.82 and 79.29 % (at pH≈7), respectively, for initial concentrations of 10, 100, 200, and 300 mg/L. The pseudo-second-order model well described the adsorption kinetics of Ni(II). The Langmuir isotherm provided the best fit to the experimental data with a maximum monolayer adsorption capacity of 59.6 mg/g. The findings of this work suggest the potential of the produced HDTMA-Ac material that can be used to remove toxic metals from wastewater.